(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2013)
Endometrial carcinoma in an infant is a very rare condition; it typically occurs in elderly patients; approximately 88% are postmenopausal at the time of diagnosis1. Classically, Endometrial carcinoma affects the obese, nulliparous, infertile, hypertensive and diabetic white women, but usually can be occur in the absence of all these factors. Estrogens are implicated as causative factor in endometrial carcinoma because a high incidence of this disease in patients with presumed attention in oestrogen metabolism and in those who take exogenous estrogens. Polycystic ovarian disease and Granulosa cell tumours of the ovary can produce high level of oestrogens but are rare cause of hyperestrogenism and endometrial carcinoma2.Gonadal dysgenesis can also be associated with endometrial adenocarcinoma3. Embrional vaginal carcinoma are most commonly seen in very young girls. The tumour usually involves the vagina , the cervix may be affected as well, particularly in an older child. Batryoids sarcoma arises from the submucosal tissue and rapidly spread beneath an intact vaginal epithelium and bulges as polypoid growth. Three types of vaginal and cervical tumour may appear during childhood & early teens, endometrial carcinoma occur most often in young children. Carcinoma arising in a remnant of a mesonephric duct occurs more often in girls of 3 yrs of age or older4. Clear cell adenocarcinoma of nulliparous origin often associated with a history of antenatal exposure of DES ( Diethylestilbestrol ). But no clear cut evidence is detected in infant or childhood endometrial carcinoma. DOI: http://dx.doi.org/10.3329/bjog.v26i1.13760 Bangladesh J Obstet Gynaecol, 2011; Vol. 26(1) : 45-47